Vergewe en vergeet: ‘n Pastorale perspektief - Dreyer, Yolanda (Verbum et ecclesia, 2005)
This article focuses on pastoral care concerning people who have been victimised by others. The aim is to highlight the theological dilemma created for such people by the Christian imperative to forgive. The article argues that pastoral care goes beyond this imperative. The focus is rather on healing and wholeness. After this has been achieved, true compassion toward others who are down-trodden and have been hurt, becomes possible. In this way forgiveness can be internalised. This pastoral approach is theoretically substantiated by the philosophy of Paul Ricoeur and the practical theology of Donald Capps.